Pelaksanaan Sita Eksekusi Kapal Laut Sebagai Jaminan Atas Pinjaman Kredit Di Indonesia Dan Singapura - Lendrawati Lendrawati; Jeffrey Jeffrey (Journal of Judicial Review, 2015)
Indonesian and Singapore as maritime state, bolstering the maritime sector in every way. One of the effort is through the financial support from the bank sector for shipping industry. And yet the effort of Indonesian and Singapore have faced many problem. The major problem is the nonperforming loan till the event of default, both state must provide legal solution for every bank sector. One of the most suitable legal solution is through the confiscation execution of the ship as credit guarantee. This method offers the most appropriate and fast solution for the bank sector to reclaim their payment from the event of default of nonperforming loan.This research is a sociological law by using the method of comparative law. Sources of data used in the form of primary and secondary data sources. Data mining is done with field research and literature study. After all the data collected, the data is then processed and analyzed, the qualitative analysis is used with the intention to classify aspects of data studied. Furthermore, it is concluded that the research associated with this, then described descriptively.Based on the results of this study showed that there are some similarities and differences in the legal procedure and application of confiscation execution of ship vessel as nonperforming loan guarantee in Indonesia and Singapore. However, in terms of legal liability, the provisions and legal principle in Singapore is better than Indonesia, seen in firmness and law certainty to solve the problem.